2014
DOI: 10.1155/2014/854093
|View full text |Cite|
|
Sign up to set email alerts
|

Stimulatory Effects of Gamma Irradiation on Phytochemical Properties, Mitotic Behaviour, and Nutritional Composition of Sainfoin (Onobrychis viciifoliaScop.)

Abstract: Sainfoin (Onobrychis viciifolia Scop. Syn. Onobrychis sativa L.) is a bloat-safe forage crop with high levels of tannins, which is renowned for its medicinal qualities in grazing animals. Mutagenesis technique was applied to investigate the influence of gamma irradiation at 30, 60, 90, and 120 Gy on mitotic behavior, in vitro growth factors, phytochemical and nutritional constituents of sainfoin. Although a percentage of plant necrosis and non-growing seed were enhanced by irradiation increment, the germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
5
22
0
Order By: Relevance
“…Similarly, there are some reports which indicate that higher doses of gamma radiation are usually inhibitory [4], whereas lower doses are sometimes stimulatory [16].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, there are some reports which indicate that higher doses of gamma radiation are usually inhibitory [4], whereas lower doses are sometimes stimulatory [16].…”
Section: Discussionmentioning
confidence: 92%
“…The percentage of spontaneous mutations is too low for breeding purposes in nature. Hence, chemical and physical mutagens can be used to encourage mutation [4]. Genetic variability is the most important requirement for effective crop development in terms of variant selection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the effected of the used gamma radiation doses on the translocation of metabolites rather than inhibition of their metabolism. The partition of the metabolites into the different plant organs was previously found to be affected by the different stresses such as gamma ray irradiation (Kim et al, 2006;Mohajer et al, 2014). Figure 5 shows that content of secondary metabolites in the whole plant, in general, acquired the trend alkaloid > phenolic > saponin compounds indicating that alkaloid content represents the major medicinal compounds in comparison with phenolic compounds and saponin of chicory plant.…”
Section: Total Phenolicsmentioning
confidence: 90%
“…Also, the remarkable accumulation of the alkaloid compounds in the plant root than in shoot showed that most treatment induced translocation of alkaloids compounds f rom shoot to root rather increase their metabolism in shoot especially under the highest treatment (80 Gy). Several studies such as those of Kim et al (2006) and Mohajer et al (2014) report that gamma irradiation significantly affects the alkaloid content of different organs in various plants. It is also important to note that 40 Gy induced both metabolism of alkaloids in shoot and their translocation from shoot to root leading to high al kaloids content in the two organs.…”
Section: Alkaloid Contentmentioning
confidence: 99%